표고 톱밥재배용 신품종 ‘화담’ 육성 및 특성 - 김정한; Jeong-han Kim; 강영주; Young-ju Kang; 백일선; Il-sun Baek; 신복음; Bok-eum Shin; 최종인; Jong-in Choi; 이용선; Yong-seon Lee; et al. (Hangug gynnhaghoi ji, 2020)
A new oak mushroom cultivar ‘Hwadam’ was bred from monokaryotic strains of ‘GMLE36062’ and ‘LE15401’. The optimum temperature for mycelial growth of ‘Hwadam’ on potato dextrose agar was 25℃. The cultivation period of ‘Hwadam’ lasted for 129 days until the first harvest of the fruiting bodies, including 35 days for spawn run, 84 days for browning, and 10 days for development of fruiting bodies. The fruiting bodies of ‘Hwadam’ had a hemispherical, brighter pileus and thicker stipe than the control cultivar (Sanjo 701ho). The three-cycle yield of ‘Hwadam’ was 554 g, which was higher than that of control cultivar (405 g). In addition, ‘Hwadam’ contained 79.4 mg/g of beta-glucan and 0.93 mg GAEs/g of phenolic compounds, which was similar to that of the control cultivar but higher than that of 'L808' and 'Chujae 2ho'.